2019
DOI: 10.3892/or.2019.7390
|View full text |Cite
|
Sign up to set email alerts
|

Novel lncRNA PSMG3‑AS1 functions as a miR‑143‑3p sponge to increase the proliferation and migration of breast cancer cells

Abstract: Long non-coding RNAs (lncRNAs) are considered to be important regulators in breast cancer. In the present study, the potential mechanisms and functional roles of lncRNA PSMG3-antisense (AS)1 were investigated in vivo and in vitro. The relative expression levels of lncRNA PSMG3-AS1 and microRNA (miR)-143-3p were determined using reverse-transcription quantitative PCR. The protein expression levels of collagen type 1 alpha 1 (COL1A1) and proliferating cell nuclear antigen (PCNA) were obtained using western blot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 39 publications
2
36
0
Order By: Relevance
“…The functionality of PSMG3-AS1 has only been investigated in breast cancer [13]. It is observed that PSMG3-AS1 is overexpressed in breast cancer and may promote the migration and proliferation of cancer cells by sponging miR-143-3p [13]. To the best of our knowledge, this study is the first to report the upregulation of PSMG3-AS1 in LUAD, a major subtype of lung cancer.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The functionality of PSMG3-AS1 has only been investigated in breast cancer [13]. It is observed that PSMG3-AS1 is overexpressed in breast cancer and may promote the migration and proliferation of cancer cells by sponging miR-143-3p [13]. To the best of our knowledge, this study is the first to report the upregulation of PSMG3-AS1 in LUAD, a major subtype of lung cancer.…”
Section: Discussionmentioning
confidence: 93%
“…In addition, miR-449b-5p might be able to target PSMG3-AS1 to suppress cancer cell proliferation. The functionality of PSMG3-AS1 has only been investigated in breast cancer [13]. It is observed that PSMG3-AS1 is overexpressed in breast cancer and may promote the migration and proliferation of cancer cells by sponging miR-143-3p [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies had shown that LncRNA was abnormally expressed in a variety of human cancers, and its abnormal expression was significantly related to the proliferation, migration, invasion of cancer cell and so on. For example, the expression of lncRNA PSMG3-AS1 was increased in breast cancer tissues and cells and Interference of PSMG3-AS1 expression can promote the expression of miR-143-3p, resulting in the weakness of proliferation and migration of breast cancer cells [5]. The expression of LINC00467 was up-regulated in HCC tissues and cells., and it could inhibit the proliferation and metastasis of HCC cells and promote apoptosis if LINC00467 was silenced [6].…”
mentioning
confidence: 98%
“…In conclusion, LINC00221 suppressed ALL cell proliferation and boosted ALL cell apoptosis via sponging miR-152-3p to up-regulate ATP2A2. regulate COL1A1 expression, thus enhancing proliferation and migration ability of breast cancer cells [7]. COL1A1-014 functions as a ceRNA in gastric cancer development via up-regulating CXCL12 and CXCR4 through interacting with miR-1273h-5p [8].…”
mentioning
confidence: 99%